Fish Gelatin: Current Nutritional, Medicinal, Tissue Repair Applications, and as a Carrier of Drug Delivery - Soliman, Amro M.; Teoh, Seong L.; Das, Srijit (Current Pharmaceutical Design, 2022)
Gelatin is obtained via partial denaturation of collagen and is extensively used in various industries. The majority of gelatin utilized globally is derived from a mammalian source. Several health and religious concerns associated with porcine/bovine gelatin have been reported. Therefore, gelatin from a marine source is widely being investigated for its efficiency and utilization in a variety of applications as a potential substitute for porcine/bovine gelatin. Although fish gelatin is less durable and possesses lower melting and gelling temperatures compared to mammal-derived gelatin, various modifications have been reported to promote its rheological and functional properties to be efficiently employed. The present review describes in detail the current innovative applications of fish gelatin involving the food industry, drug delivery, and possible therapeutic applications. Gelatin bioactive molecules may be utilized as carriers for drug delivery. Due to its versatility, gelatin can be used in different carrier systems, such as microparticles, nanoparticles, fibers, and hydrogels. The present review also provides a perspective on the other potential pharmaceutical applications of fish gelatin, such as tissue regeneration, antioxidant supplementation, and antihypertensive and anticancer treatments.
Keywords: biomedical applications